A new digital signal processing (DSP) evaluation board for real time application - Chieng, Wee Kai (2010)
This project has a final goal of designing a new digital signal processing (DSP) evaluation board for real time application. DSP encompasses the digital representation of signals and the digital hardware to analyze, modify, extract information from digital signals. An evaluation board is a general purpose board with an embedded processor and generally with a way to download and execute user's program on it. Real time application places stringent demands on hardware and software design to complete predefined tasks within a certain time frame. This project consists of both hardware and software developments. The evaluation board accepts audible sounds (less than 10kHz) as its inputs and performs real time frequency and time domain transformation, frequency filtering and shifting operation. The results are designed to be outputted through computer screen and speaker. In this project, schematic is designed using Cadence Orcad v16.2 Capture, layout is designed using Cadence Orcad v16.2 PCB designer, programmer is developed under Microchip MPLAB IDE v8.46, DSP programs are developed by using Microchip C30 combo lite edition v3.23 tool suite and computer reception programs are developed by using Microsoft Visual C# 2008 express edition. This project was scheduled for two semester in which the activities of project requirements determination, embedded cores selection, modules planning, schematic design, component footprint checkup and layout design were done in first semester whereas activities to fabricate PCB board, solder components, set up programmer, develop software programs, validate output were carried out in semester 2. Experiment results prove that the project objectives have been fulfilled and problem statements have been solved.